A Bibliography of Work on and by Alain Badiou in English - Paul Ashton (Cosmos and History : the Journal of Natural and Social Philosophy, 2006)
pThis bibliography presents a complete list of the work on and by Badiou currently available (as of 1/10/2006) in English. The bibliography separates the works by Badiou (further broken into the sub-sections: Books, Collections of Essays, and Essays and Interviews), from the lsquo;Commentaries on Badioursquo;s Workrsquo;./p